2009
DOI: 10.1111/j.1439-0507.2009.01741.x
|View full text |Cite
|
Sign up to set email alerts
|

Biotype stability of Candida albicans isolates after culture storage determined by randomly amplified polymorphic DNA and phenotypical methods

Abstract: Typing methods to evaluate isolates in relation to their phenotypical and molecular characteristics are essential in epidemiological studies. In this study, Candida albicans biotypes were determined before and after storage in order to verify their stability. Twenty C. albicans isolates were typed by Randomly Amplified Polymorphic DNA (RAPD), production of phospholipase and proteinase exoenzymes (enzymotyping) and morphotyping before and after 180 days of storage in Sabouraud dextrose agar (SDA) and sterilised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 37 publications
0
12
0
6
Order By: Relevance
“…When the DNA extraction cannot be immediately performed after collection and transportation, storage becomes an alternative. In this regard, studies have demonstrated that the DNA can be extracted after up to 180 days of storage for epidemiological purposes when C. albicans are stored in SDA (Bacelo et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…When the DNA extraction cannot be immediately performed after collection and transportation, storage becomes an alternative. In this regard, studies have demonstrated that the DNA can be extracted after up to 180 days of storage for epidemiological purposes when C. albicans are stored in SDA (Bacelo et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…C. albicans is an important cause of nosocomial infections; however, in the last decade, non- albicans species were responsible for an increasing number of infections (Bacelo et al 2010, Nawrot et al 2013). Yeasts are members of the normal microflora of the skin, mucous membranes and gastrointestinal tract in healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the RAPD has been one of the most used for typing different microorganisms, such as Candida albicans (3,22).…”
Section: Fungi Of the Genusmentioning
confidence: 99%